KEEFEKTIFAN MODEL PEMBELAJARAN CPS (CREATIVE PROBLEM SOLVING) DENGAN MEDIA APLIKASI KAHOOT BERORIENTASI PADA KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS VII MTs PESANTREN DARUL IHSAN SALOHE - Magfirah Magfirah; Ismail Ismail; fitriani fitriani (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The Effectiveness of the CPS (Creative Problem Solving) Learning Model with the Kahoot Application Media Oriented to the Problem Solving Ability of Class VII Students of MTs. Darul Ihsan Salohe Boarding School. Thesis, Sinjai: Tadris Mathematics (TM) Study Program, Faculty of Tarbiyah and Teacher Training, Islamic Institute of Muhammadiyah (IAIM) Sinjai, 2021. This study aims to test the effectiveness of the CPS (Creative Problem Solving) learning model with the ability-oriented Kahoot application media problem-solving for class VII students of the Islamic boarding school Darul Ihsan Salohe. This research is experimental research using a quantitative approach. The subjects of this study were students of Class VII MTs. Darul Ihsan Salohe Boarding School. The methods of data collection were tests, questionnaires, observation, and documentation. Meanwhile, the data analysis used Descriptive Statistics and Inferential Statistical Analysis. The results showed that the CPS (Creative Problem Solving) Learning Model with the Kahoot application media using the Paired sample t-test was found that a sig value of 0.000 <0.05, it can be said to be effective. The effectiveness criteria based on the results of the n-gain is 0.254 and is in the low category. This is also supported by the test results of students' problem-solving abilities after the application of the CPS (Creative Problem Solving) learning model is better than the test results before the application of the CPS (Creative Problem Solving) learning model, student activities in CPS (Creative Problem Solving) learning are in the category high, and student responses to CPS (Creative Problem Solving) learning are positive.